New Zealand's fair pay agreements: a new direction in sectoral and occupational bargaining. (3rd July 2021) - Kent, Avalon
ABSTRACT: New Zealand is developing a new system of industry and occupational collective bargaining, called Fair Pay Agreements, aiming to establish negotiated terms, conditions and standards across specified industries, sectors or occupations. This article describes the proposal, its genesis and content, including how it will interact with other bargaining and wage-setting machinery in New Zealand. The article considers several important issues that remain to be determined including whether the system will be compulsory or voluntary; the determination of participating bargaining parties and their representation; whether FPA provisions will be extended to contractors or limited to employees; the extent of exemptions or flexibility; and the extent and nature of arbitration. The article considers whether FPAs have the potential to transform industrial relations in New Zealand, and contribute to a reinvigoration of collectivism in employment relationships. Finally, the article provides some international comparisons between the FPA proposal and models of sectoral standard-setting in other countries.